The Effect Of Using Geometer's Sketchpad SoftwareTowards Students' Mathematical Communication Skills - Awalludin, Subhan Ajiz; Adirakasiwi, Alpha Galih (CV. Inara, 2021)
Students’ mathematical communication skills in Indonesia are still under expectation. The purpose of this study is to know the effect of using Geometer's Sketchpad Software to students’ mathematical communication skill. Collecting data was done using developed mathematical communication instrument. Moreover, 63 students were participated ini this study. The proposed hypothesis in this study is there is an effect in using Geometer's Sketchpad Software to the students’ mathematical communication skills. The independent variable in this research was Software Geometer's Sketchpad, while the dependent variable was mathematical communication ability. The results shows that there is an effect of using Geometer's Sketchpad Software to the students’ mathematical communication skill.